PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) DAN DAMPAK CORPORATE SOCIAL RESPONSIBILITY (CSR) TERHADAP REAKSI INVESTOR (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2010-2013) - Iva Rizki Lestari, 11.05.52.0069; Badjuri, Achmad (Students Journal of Accounting and Banking, 2015)
This study aims to determine the effect of company characteristics on the disclosure of corporate social responsibility (csr) and the impact of corporate social responsibility (csr) of the investor reaction. Population in this research are manufacturing companies listed in Indonesia Stock Exchange 2010-2013. The sample in this study were taken by purposive sampling method. Data were analyzed using multiple regression analysis. Results of the analysis showed that the variables that have an influence on the disclosure sognifikan social responsibility is profitability, company profiles and commissioners. While the size of the company, the companys ownership does not affect the disclosure of social responsibility and social responsibility disclosure does not affect the reaction of investors.Keywords: Company Size, Profitability, Company Profile, Board of Directors, Ownership of The Company, Investor Reaction